MANAGERIAL COMPETENCIES OF PRINCIPALS AND THE INTERNATIONAL ORGANIZATION FOR STANDARDIZATION ISO 9001:2000 IN IMPROVING THE TEACHER WORK DISCIPLINE - MUBARAK, Zaki (JKP | Jurnal Kepemimpinan Pendidikan, 2019)
The study aims to identify, analyze, and test the effect of managerial skills of school principals to teachers’ work discipline, the effect of the implementation of ISO 9001: 2008 to the teacher work disicipline, and the influence of the principal managerial ability to imlementasi policy quality ISO 9001: 2008. The study used survey methods, with path analysis techniques. Population of 156 teachers, sample 112 teachers. Data were collected through questionnaires, scale Likert. The results showed that: 1) There is a direct positive effect managerial skills of school principals to discipline teachers’ work, with the coefficient correlation 0,897, determination of the coefficient of 0,805; 2) There is a direct positive effect of ISO 9001: 2008 to the discipline teacher work, with the coefficient correlation 0,307, determination of the coefficient of 0,095; 3) There is a direct positive effect managerial skills of school principals to ISO 9001: 2008, with the coefficient correlation 0,340, determination of the coefficient of 0,116. In conclusion, the influence of managerial ability of the principal and the implementation of ISO 9001:2008 against disciplined teachers work has a fairly high level of significance.